2018
DOI: 10.3389/fimmu.2018.00200
|View full text |Cite
|
Sign up to set email alerts
|

IL-36γ Is a Strong Inducer of IL-23 in Psoriatic Cells and Activates Angiogenesis

Abstract: The IL-1 family member cytokine IL-36γ is recognised as key mediator in the immunopathology of psoriasis, hallmarks of which involve the activation of both resident and infiltrating inflammatory myeloid cells and aberrant angiogenesis. This research demonstrates a role for IL-36γ in both myeloid activation and angiogenesis. We show that IL-36γ induces the production of psoriasis-associated cytokines from macrophages (IL-23 and TNFα) and that this response is enhanced in macrophages from psoriasis patients. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 93 publications
1
58
1
Order By: Relevance
“…A recent study showed that another key inflammatory cytokine that drives neutrophil migration in GPP is the IL-36 family of cytokines (12), which mainly functions on keratinocytes and myeloid dendritic cells. For instance, several reports have indicated IL-36g acts as a potent proinflammatory mediator and a valuable biomarker of disease activity in psoriasis pathogenesis (45)(46)(47). The IL-36 cytokine family can increase the expression of chemokines including CXCL1, CXCL8, CCL3, CCL5, and CCL20 in keratinocytes to induce the infiltration of more activated leukocytes (48).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that another key inflammatory cytokine that drives neutrophil migration in GPP is the IL-36 family of cytokines (12), which mainly functions on keratinocytes and myeloid dendritic cells. For instance, several reports have indicated IL-36g acts as a potent proinflammatory mediator and a valuable biomarker of disease activity in psoriasis pathogenesis (45)(46)(47). The IL-36 cytokine family can increase the expression of chemokines including CXCL1, CXCL8, CCL3, CCL5, and CCL20 in keratinocytes to induce the infiltration of more activated leukocytes (48).…”
Section: Discussionmentioning
confidence: 99%
“…The possible involvement of IL‐36 signalling has recently gained attention in the pathogenesis of psoriasis . Besides acting as a psoriatic biomarker, loss‐of‐function mutations in the IL‐36R antagonist (IL‐36RN) were identified in multiple cohorts of generalized pustular psoriasis patients .…”
Section: Discussionmentioning
confidence: 99%
“…Besides acting as a psoriatic biomarker, loss‐of‐function mutations in the IL‐36R antagonist (IL‐36RN) were identified in multiple cohorts of generalized pustular psoriasis patients . IL‐36γ regulates keratinocyte proliferation and differentiation to promote skin wound healing, and acts on tissue infiltrating macrophage and actively promotes recruitment of monocytes which cumulatively amplify IL‐23 expression, thus promoting polarization of lymphocytes for increased IL‐17A expression . In psoriasis, keratinocytes are major source of IL‐36γ, and previous observations showed that IL‐36γ had the highest expression level in damaged skin .…”
Section: Discussionmentioning
confidence: 99%
“…The IL‐36 family cytokines consist of Il‐36α, IL‐36β, and IL‐36γ. These cytokines are members of the wider IL‐36 family and are associated with the psoriatic skin inflammation . IL‐36 has inflammatory effects on a range of cells including stroma, T‐cells, fibroblast, and myeloid cells .…”
Section: The Concept Of Il‐23–independent Il‐17 Productionmentioning
confidence: 99%
“…IL‐36 has a growing role in regulating the IL‐23/IL‐17 axis in several diseases . In addition to inducing IL‐23 from myeloid cells, IL‐36 also promotes T‐cell proliferation . Like PsA patients, DITRA patients also benefit from monocyte apheresis treatment .…”
Section: The Concept Of Il‐23–independent Il‐17 Productionmentioning
confidence: 99%